Multiple Health Behavior Programs in School Settings: Strategies to Promote Transfer-of-Learning Through Life Skills Education - Veronica Velasco; Corrado Celata; Kenneth W. Griffin; Estensione LST group (Frontiers Media S.A., 2021)
Typically, schools implement health promotion programs that focus on a single behavioral domain. Multiple related health topics may be addressed using separate interventions, potentially producing overlap in program content. However, integrative approaches in health promotion have the potential to produce interventions capable of improving multiple health behaviors. In particular, more research is needed to identify the conditions and the factors that can promote the transfer of learning to broaden the target outcomes of health promotion programs. The present study aims to identify the characteristics of an evidence-based life skills education program that can facilitate the transfer of learning to different health behaviors not initially targeted by the program, and the strategies for achieving successful transfer. A two round Delphi method was used with a diverse group of 21 experts in health promotion, life skills education, and methods of pedagogy for early adolescent students. Questionnaires with open and closed-ended questions were administered on-line. Content qualitative analysis was run, integrating codes, subcategories, and categories of the two rounds of the study. Results showed strong consensus among experts about the potential for promoting the transfer of skills from one health domain to another. Many elements were identified as important factors that facilitate the transfer of learning. Strategies for successful transfer were related to teaching methods, educational approaches, and consistency with the broader school curriculum. Findings suggest that the successful transfer of learning to a new health domain requires that educators recognize its importance and explicitly designate it as an educational aim.